Matrix metalloproteinase-7 is dispensable in a mouse model of sepsis-induced acute lung injury - Brandon Baer; Jason Lin; Kaitlyn R. Schaaf; Lorraine B. Ware; Ciara M. Shaver; Julie A. Bastarache (PLoS ONE, 2025)
Acute respiratory distress syndrome (ARDS) is a life-threatening form of acute lung injury whose pathogenesis is characterized by excessive lung inflammation and alveolar-capillary barrier permeability. Matrix metalloproteinase 7 (MMP7) can regulate leukocyte recruitment and the production of pro-inflammatory cytokines, but whether it plays a role in acute lung injury (ALI) is an unanswered question. We hypothesized that global loss of MMP7 would attenuate sepsis-induced ALI and systemic inflammation. To test this, male and female MMP7 knockout (MMP7KO) mice and wild-type (WT) littermates were exposed to a two-hit model of ALI (sepsis+hyperoxia). Sepsis was induced through intraperitoneal injection of cecal slurry (CS; 1.6mg/g) or 5% dextrose (control) followed by exposure to hyperoxia (HO; FiO2=0.95) or room air (control, FiO2=0.21). At 24-hours post-CS+HO, we measured weight loss, illness severity, and body temperature. The mice were then sacrificed, and samples from the lungs, kidneys, spleen, blood, peritoneal wash, and bronchoalveolar lavage (BAL) fluid were collected for analysis. Bacterial burden was assessed in the peritoneum, lung, and spleen. Lung inflammation was assessed by BAL inflammatory cell recruitment and pro-inflammatory cytokine concentrations as well as lung tissue mRNA expression of pro-inflammatory cytokines. Alveolar-capillary barrier disruption was quantified by BAL total protein, BAL immunoglobulin M, and lung wet-to-dry weight ratios. Histologic evidence of lung injury was evaluated using a histological scoring system. Systemic inflammation was measured through plasma pro-inflammatory cytokines and peritoneal inflammatory cells. Kidney function, inflammation, and injury were assessed through plasma urea nitrogen concentrations, as well as tissue levels of pro-inflammatory cytokines, neutrophil gelatinase-associated lipocalin (NGAL), and kidney injury molecule 1 (KIM-1). Relative mRNA expression of MMP-7, MMP-9, and MMP-2 was also quantified in both lung and kidney tissue through qPCR. At 24-hours post-CS+HO all mice developed ALI. Septic mice also had increased systemic inflammation, kidney inflammation, kidney injury, and kidney dysfunction compared to controls. Loss of MMP7 did not affect markers of inflammation, organ injury, or organ dysfunction. Interestingly, septic male mice exhibited more severe illness, systemic and lung inflammation, lung injury, and lung expression of matrix metalloproteinases, while septic female mice exhibited more kidney inflammation, kidney injury, and kidney expression of matrix metalloproteinases. In conclusion, MMP7 is not essential for the development or resolution of sepsis-induced ALI in this model and likely plays a limited role in the condition.